Effect of coagulants and flocculants in the removal of turbidity from polluted river waters (Agroindustrial Science, 2024)
The objective of the research work was to evaluate coagulants and flocculants in the removal of turbidity from polluted river waters, three natural coagulants were used: Moringa oleífera, Musa paradisiaca (silk variety banana pith), Theobroma Cacao (Cacao mucilage of the Criollo variety ) and aluminum sulfate (Al2SO4) at a single concentration of 50 ppm and through a jar test, a rapid mixture of 200 rpm for 1 min was established, then at 45 rpm for 15 min and a sedimentation time of 15 min. The behavior of the water quality indicators was obtained as a result: turbidity, biological oxygen demand (BOD5), electrical conductivity, total suspended solids and total dissolved solids, before and after carrying out the treatments, using the Duncan test. determined the best treatment for Moringa oleifera presenting an average turbidity removal of 92.15% and aluminum sulfate an average turbidity removal of 90.70%, concluding that Moringa oleifera is an alternative to replace aluminum sulfate due to its reduced toxicity and environmental viability.
Keywords: Coagulants; flocculants; removal; turbidity; drinking water